INDONESIAN FIQH IN RESOLVING CONTEMPORARY PROBLEMS “Menggagas Kembali Fiqh Indonesia Dalam Bingkai Masyarakat Multikultural di Era Globalisasi” - Muniri, Akhmad Syamsul (Et-Tijarie, 2015)
Departing from the view Hasbi ash-Shiddiqy who want to form Fiqh Indonesia by using all existing legal schools (muqaranah al-madzahib) as the base material as well as a major source of material and Hazarin for the creation of national schools of fiqh (Indonesia) departing only from development Shafi'i fiqh schools, then in this paper in this globalization era author wants to initiate re-Fiqh Indonesia by using all existing schools of law globally, or more broadly in this paper multicultural society menghasilakn conclusion that Indonesian fiqh initiated back in the frame in the multicultural society the era of globalization is a long discourse dealt with by the experts of Islamic law so it needs no development using global law schools. Generally they argue, Shari'ah contained in the Quran and al-Sunnah should be understood as an ethical and moral norms are universal and applicable to all societies, across ethnicity, race, culture, customs and even religion though.